2017
DOI: 10.1108/imds-02-2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

The impact of leadership on trust, knowledge management, and organizational performance

Abstract: Purpose The purpose of this paper is to build a research model that examines the impact of leadership on trust, knowledge management and organizational performance. Design/methodology/approach An instrument containing six constructs (leadership: leading organization; leadership: leading people; leadership: leading self, trust, knowledge management and organizational performance) was designed and administered to subjects from all levels of management in various organizations in nine regions of the USA. Collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 78 publications
6
103
1
1
Order By: Relevance
“…From the research results, the respondents concurred that the managers encourage employees to ask questions when they have things that they do not understand, articulate information and data across the organization, and express enthralling and captivating vision, and strategies so that employees take part in cross-border knowledge transfer. When managers and leaders are very encouraging to their subordinates in terms of exchanging information, it reduces the psychological barriers that prevent them from approaching their Japanese counterpart (Koohang et al, 2017). This allows a working environment that is open and flexible where people can teach and learn freely.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the research results, the respondents concurred that the managers encourage employees to ask questions when they have things that they do not understand, articulate information and data across the organization, and express enthralling and captivating vision, and strategies so that employees take part in cross-border knowledge transfer. When managers and leaders are very encouraging to their subordinates in terms of exchanging information, it reduces the psychological barriers that prevent them from approaching their Japanese counterpart (Koohang et al, 2017). This allows a working environment that is open and flexible where people can teach and learn freely.…”
Section: Resultsmentioning
confidence: 99%
“…According to Taka and Foglia (1994), Japanese business affiliates' management leadership style such as self-realization, appreciation of diverse abilities and trust in others play crucial role in fostering strong learning intention. Likewise, Koohang et al (2017) study found that effective leadership styles can bring out the engagement and enthusiasm in employees to learn. Therefore, leadership style has been studied as another aspect of knowledge context to determine if it positively affects the effectiveness of Japanese business affiliates' cross-border knowledge transfer in Malaysia.…”
Section: Leadershipmentioning
confidence: 95%
See 1 more Smart Citation
“…Organizational performance shows the development and progress of an organization [45]. The analysis of organizational success is one of the most investigated variables.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Knowledge management can be defined as the purposeful and systematic management of processes, methods, and tools, making full use of the organisation's knowledge potential to form goals, make efficient decisions, create and implement the uniqueness and value of the organization. Scientists, when examining the process approach to knowledge management, distinguish between different combinations of knowledge management processes (Wiig, 1993;Meyer & Zack, 1996;Mcelroy, 1999;Probst, Raub, & Romhardt, 2000;Rollett, 2003;Becerra-Fernandez, Gonzalez, & Sabherwal, 2004;Lin & Lee, 2005;Franco & Mariano, 2007;Supyuenyong, Islam, & Kulkarni, 2009;Sun, 2010;Dalkir, 2011;O'Dell & Hubert, 2011;Pinho, Rego, & Pina e Cunha, 2012;Rusly, Corner, & Sun, 2012;Wee & Chua, 2013;Agarwal & Islam, 2014;Bigliardi, Galati, & Petroni, 2014;Obeidat, Masa' deh, & Abdallah, 2014;Ranjbarfard, Aghdasi, López-Sáez, & López, 2014;Chang & Lin, 2015;Hegazy & Ghorab, 2015;García-Fernández, 2015;Tubigi & Alshawi, 2015;Wahba, 2015;Costa & Monteiro, 2016;Hwang, 2016;Kianto, Vanhala, & Heilmann, 2016;Nowacki & Bachnik, 2016;Acar, Tarim, H. Zaim, S. Zaim, & Delen, 2017;Bican, Guderian, & Ringbeck, 2017;Chhim, Somers, & Chinnam, 2017;Koohang, Paliszkiewicz, & Goluchowski, 2017;Yusr, Mokhtar, Othman, & Sulaiman, 2017;Dzenopoljac...…”
Section: Introductionmentioning
confidence: 99%